STUDY ON OPTIMIZATION OF REMANUFACTURING OF HYDRAULIC SUPPORT COLUMN - XIE Miao; CAO LiPing; TIAN Bo; LIU Xuan (Jixie qiangdu)
A parameters optimization of a hydraulic support column remanufacturing method was studied in this paper. The mathematical model of the radial shrinkage of the coating was established by using the constitutive equation,the geometric equation and the relation between the linear expansion coefficient and the temperature variation. The effect of material,coating thickness and assembly temperature on the radial shrinkage of the coated layer and the range of research parameters were analyzed by MATLAB software.The RAMP interpolation model was used to interpolate the material parameters. The optimization model was set up and the optimization solution process was designed. The post column was taken as an example.The thickness of the coating is reduced by 0. 5 mm.The assembly temperature is reduced by 80 degree Celsius and the radial shrinkage force is increased by 0. 0195 N/mm~2. The optimized remanufactured column can reduce the 0. 13 mm and 0. 11 mm,respectively,under the working condition of the conveyer and the moving frame.